Delineation of Information Retrieval Research Area Using Input-Output Model - Tabatabaei, Nahid; Beheshti, Jamshid (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Information Retrieval (IR) research has been one of the core research areas of Information Science (IS) and also a major source of interdisciplinary relations between IS and other disciplines, constituting a disjointed research area with fuzzy boundaries. The main purpose of this paper is to identify disciplines that contribute to IR research and to map the main features of the interdisciplinary structure of IR research area as a whole. La recherche dans le domaine du repérage d’information (RI) a toujours été un domaine-clé des sciences de l’information (SI) et également une source majeure de relations interdisciplinaires entre les SI et d’autres disciplines, constituant un domaine de recherche incohérent aux frontières floues. Le principal objectif de cette communication est d’identifier les disciplines qui contribuent à la recherche en RI et de mettre en correspondance les principales caractéristiques de la structure interdisciplinaire de la recherche en RI, de manière à constituer un tout.